Decolorization and Mineralization of Remazol Red F3B by Fenton and Photo-Fenton Processes - Saatci, Yusuf (Asce-Amer Soc Civil Engineers, 2010)
Degradation of aqueous solutions of a commercial azo-reactive textile dye, Remazol Red F3B, by the Fenton and photo-Fenton processes, has been investigated. Fenton-type reaction rates are strongly dependent on pH, temperature, and initial concentrations of the Fe(2+), H(2)O(2), and dye. The effects of varying these parameters on the degradation performances of these two processes have been studied, and the optimal operational conditions have been found. The optimal conditions for these processes were obtained at pH=3. A comparative study of the Fenton and photo-Fenton reactions has also been carried out using a photoreactor. The Fenton process is highly efficient for removal of the color, chemical oxygen demand, and total organic carbon of a Remazol Red F3B solution. The photo-Fenton process proved to be more efficient, and proceeds at a much higher oxidation rate than the Fenton process. The photo-Fenton process allows 90% degradation of chemical oxygen demand in about 20 min of reaction time.
Keywords: Azo dye; Remazol Red F3B; Decolorization; Mineralization; Fenton; Photo-Fenton